Analysis of microRNA Expression Profiles Induced by Yiqifumai Injection in Rats with Chronic Heart Failure - Zhao, Yu; Li, Yunfei; Tong, Ling; Liang, Xinying; Zhang, Han; Li, Lan; Fan, Guanwei; Wang, Yi (Frontiers in Physiology, 2018)
Background: Yiqifumai Injection (YQFM) is clinically used to treat various cardiovascular diseases including chronic heart failure (CHF). The efficacy of YQFM for treating heart failure has been suggested, but the mechanism of action for pharmacological effects of YQFM is unclear. Methods: Echocardiography detection, left ventricular intubation evaluation, histopathology and immunohistochemical examination were performed in CHF rats to evaluate the cardioprotective effect of YQFM. Rat miRNA microarray and bioinformatics analysis were employed to investigate the differentially expressed microRNAs. In vitro models of AngII-induced hypertrophy and t-BHP induced oxidative stress in H9c2 myocardial cells were used to validate the anti-hypertrophy and anti-apoptosis effects of YQFM. Measurement of cell surface area, ATP content and cell viability, real-time PCR and Western blot were performed. Results: YQFM significantly improved the cardiac function of CHF rats by increasing left ventricular ejection fraction and fractional shortening, decreasing left ventricular internal diameter and enhancing cardiac output. Seven microRNAs which have a reversible regulation by YQFM treatment were found. Among them, miR-21-3p and miR-542-3p are related to myocardial hypertrophy and cell proliferation, respectively and were further verified by RT-PCR. Target gene network was established and potential related signaling pathways were predicted. YQFM could significantly alleviate AngII induced hypertrophy in cellular model. YQFM also significantly increased cell viabilities and ATP content in t-BHP induced apoptosis model. Western blot analysis showed that YQFM could increase the phosphorylation of Akt. Conclusion: Our findings provided scientific evidence to uncover the mechanism of action of YQFM on miRNAs regulation against CHF by miRNA expression profile technology. The results indicated that YQFM has a potential effect on alleviate cardiac hypertrophy and apoptosis in chronic heart failure.